Controlled Formation of Dimers and Spatially Isolated Atoms in Bimetallic Au‐Ru Catalysts via Carbon‐Host Functionalization. Issue 15 (27th February 2022) - Giulimondi, Vera; Kaiser, Selina K.; Martín, Antonio J.; Büchele, Simon; Krumeich, Frank; Clark, Adam H.; Pérez‐Ramírez, Javier
Abstract: The introduction of a foreign metal atom in the coordination environment of single‐atom catalysts constitutes an exciting frontier of active‐site engineering, generating bimetallic low‐nuclearity catalysts often exhibiting unique catalytic synergies. To date, the exploration of their full scope is thwarted by (i) the lack of synthetic techniques with control over intermetallic coordination, and (ii) the challenging characterization of these materials. Herein, carbon‐host functionalization is presented as a strategy to selectively generate Au‐Ru dimers and isolated sites by simple incipient wetness impregnation, as corroborated by careful X‐ray absorption spectroscopy analysis. The distinct catalytic fingerprints are unveiled via the hydrogen evolution reaction, employed as a probe for proton adsorption properties. Intriguingly, the virtually inactive Au atoms enhance the reaction kinetics of their Ru counterparts already when spatially isolated, by shifting the proton adsorption free energy closer to neutrality. Remarkably, the effect is magnified by a factor of 2 in dimers. These results exemplify the relevance of controlling intermetallic coordination for the rational design of bimetallic low‐nuclearity catalysts. Abstract : Carbon functionalization controls intermetallic bond formation in Au‐Ru low‐nuclearity catalysts (LNCs), yielding isolated atoms in the presence of N‐functionalities and dimers in their absence. Distinct electronic fingerprints are unveiled via the hydrogen evolution reaction. While Au promotes the activity of Ru in both configurations, the effect is magnified in dimers, highlighting the importance of intermetallic coordination in bimetallic LNC design.